2016
DOI: 10.4254/wjh.v8.i35.1557
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C eradication with sofosbuvir leads to significant metabolic changes

Abstract: AIMTo assess the effect of sofosbuvir (SOF) based regimens on glycemic and lipid control.METHODSThis is a retrospective analysis of hepatitis C virus (HCV)-infected patients treated and cured with a SOF regimen [SOF/ribavirin/interferon, SOF/simeprevir, or SOF/ledipasvir (LDV) ± ribavirin] from January 2014 to March 2015. Patients with hemoglobin A1C (HbA1C) and lipid panels within six months before and six months after therapy were identified and included in our study. Due to the known hemolytic effect of rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 39 publications
7
43
0
2
Order By: Relevance
“…This is in agreement with several studies [12,[15][16][17]. Abdel Alem et al, found a reduction in both FBS and HbA1c after HCV eradication [18].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in agreement with several studies [12,[15][16][17]. Abdel Alem et al, found a reduction in both FBS and HbA1c after HCV eradication [18].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, some cases were reported to stop insulin therapy after viral eradication [19]. Similarly, Morales et al, proved the reduction of HbA1c in patients with T2DM after treatment with DAA but they failed to explain this improvement [12]. They suggested an improvement of IR after eradication of HCV.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other study reported a lipid increase in posttreatment (15) . Concerning DAAs, recent studies suggest that TC and LDL serum levels increase after the end of treatment, whereas triglyceride levels decrease (16,17,18,19) . However, the behavior of serum levels along with the sustained virologic response is not yet clear, that is, whether the relapse or the non-response to treatment could be accompanied by these lipidic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Several other small retrospective studies [12][13][14][15] have shown a significant improvement of fasting plasma glucose and of glycated hemoglobin A1C in patients who achieved SVR with DAA treatment.…”
mentioning
confidence: 99%